Analisis Strategi Pengembangan Usaha Guna Meningkatkan Modal Kerja dan Keuntungan di Perusahaan Roti Tiga Berlian Kota Lubuklinggau - Wisdalia Maya Sari; Fitria Fitria; Prilia Dwi Hartina (Journal of Management and Bussines (JOMB), 2019)
The purpose of this study is to determine the working capital in the company under study, find out the company's profits in the research site, make a company development strategy. This research was conducted at the Roti Tiga Berlian company in the City of Lubuklinggau. The method used in this research is quantitative descriptive method with working capital, profit and SWOT analysis. The results of this study are that the capital system is put to good use, working capital management has gained profits, recommendations for company development, namely: 1) increasing the understanding of bread variants; 2) opening factories in strategic areas; 3) build special otlets for three-diamond bread products. Conclusion, the condition of the Lubuklinggau City Tiga Berlian Bread Company in managing working capital owned to obtain profit is in a healthy condition, so that for 5 (five) years it is known that it is able to use the working capital owned to obtain profit Keywords: Development Strategy, Working Capital, Profit